Removal and Recovery of Cr(VI) from Industrial Plating Wastewater Using Fibrous Anion Exchanger - Lee, Chang-Gu; Park, Jeong-Ann; Choi, Jae-Woo; Ko, Seok-Oh; Lee, Sang-Hyup (Kluwer Academic Publishers, 2016)
The aim of this study was to investigate the removal and recovery of hexavalent chromium (Cr(VI)) from industrial plating wastewater using anion exchanger Kanecaron SA fibers in batch systems. The surface morphology and physicochemical properties of the fiber were analyzed by scanning electron microscopy (SEM), energy-dispersive X-ray analysis (EDAX), and Fourier transform infrared spectroscopy (FT-IR). The removal efficiency was affected by the solution pH and showed a plateau formation decreasing on both sides of pH 4. The Cr(VI) uptake on Kanecaron SA fibers was rapidly increased in the first 10 min, and the kinetic data fit well to the Elovich model. Isotherm model analysis demonstrates that the Redlich-Peterson model suitably describes the equilibrium data, and the maximum adsorption capacity (Q(m)) from the Langmuir model was 87.366 mg/g for Cr(VI) in distilled water, 117.977 mg/g for total Cr, and 57.101 mg/g for Cr(VI) in wastewater. Additionally, the Cr(III) contained in the plating wastewater was removed by the Kanecaron SA fibers, while the other heavy metals were not removed. Thermodynamic analysis indicates that Cr(VI) adsorption to Kanecaron SA fibers decreased with increasing temperature from 10 to 50 degrees C, indicating the spontaneous and exothermic nature of the sorption process. The removal efficiency was maintained above 80 % during four regeneration cycles.